Cloud Portability and Interoperability: Issues and Current Trends - Di Martino, Beniamino (Springer, 2015)
This book offers readers a quick, comprehensive and up-to-date overview of the most important methodologies, technologies, APIs and standards related to the portability and interoperability of cloud applications and services, illustrated by a number of use cases representing a variety of interoperability and portability scenarios.